Impact of Wind Farm Location on Voltage Stability - Naser, I.S.; Alsharif, Mohamed; Rafa, Adel Hamad; Ahmed, Abdussalam Ali (Journal of Pure & Applied Sciences, 2021)
Recently, the use of wind farm in power systems is increasing rapidly it is having a more noticeable impact on the manner in which these power systems operate. When large wind farms are connected to a power system network, voltage stability is a concern as it affects system operation. This paper investigates the impact of wind farm location on voltage stability in power system network when the reactive power limitation of wind generators is taken into consideration and a system reaches its maximum loading. An IEEE-14 bus test system was modified by connecting wind farms to the system at different buses, with different connection scenarios at different wind penetration levels, and the wind farm consists of several variable speed doubly fed induction generator (DFIG) wind turbines. In addition, a voltage collapse proximity indicator (VCPI), based on network loadability, is employed to investigate the contribution of wind generator location to voltage stability. The results of this paper show that system voltage stability is affected positively or negatively depending on the location of wind farm.